PROGRAM PEMBERANTASAN BUTA AKSARA PADA MASYARAKAT DESA CITERAS - Puput Puspitorini; Rizal Hidayatullah (Batara Wisnu : Indonesian Journal of Community Services, 2021)
Student Work Lecture is a dedication carried out by students to the surrounding community. The ultimate goal of the implementation of KKM is to create moral students and have maturity according to their knowledge and an effort to realize education that comes from direct experience by students. Not only theoretical but the practice and application of the theory that has been studied. KKM activities are expected to provide experience to students to see the community environment directly. Moreover, can see the problems that exist in the community, so it is required that students think to solve these existing problems. The expected results of the implementation of this activity include bridging students to the world of work,